A Novel Constraints Reduction-Based Optimal Relay Coordination Method Considering Variable Operational Status of Distribution System with DGs - Purwar E.; Vishwakarma D.N.; Singh S.P. (My University, 2025)
One of the factors that affect the level of fault currents is the number of short-circuit MVA sources present during the fault. A distribution system with distributed generators (DGs) is a multi-source system, in which DGs can be connected or disconnected to meet the high or low load requirements respectively. Also, during fault conditions, DGs can get disconnected due to their low fault ride-through capabilities. These changes in connections change the number of DGs and the operational status of the system, which in turn change the fault currents seen by relays and the ranges of maximum and minimum fault currents for which the relays settings work coordinately. This paper realizes that an increase in the proliferation of DGs makes the relay coordination problem a highly constrained optimization problem, and changes in the number of DGs make the problem more complex, which can decelerate the overall performance of relays. The aim of this paper is to reduce the complexity and design a fast, robust, and adaptive protection scheme which can efficiently work in the variable environment of the DG-distribution system. This paper proposes a novel constraints reduction-based relay coordination method which selects a small set of constraints out of large set of constraints while determining the optimal relays settings. The relay coordination problem is formulated as a linear programming problem. The performance of the proposed method is tested on the both configurations, radial and meshed, of the IEEE 38-bus distribution system. Comparative studies have been conducted to highlight the advantages of the proposed approach under changing system's configuration with variable locations and sizes of DGs. © 2010-2012 IEEE.